The North End revisited : photographs - Gillmor, Alison; Melnyk, George; Osborne, J. S. (James Stephen), 1947- (University of Manitoba Press, 2017)
"Cities and the people who live in them are enduring subjects of photography. Winnipeg's North End is one of North America's iconic neighbourhoods, a place where the city's unique character and politics have been forged. First built when Winnipeg was the "Chicago of the North," the North End is the great Canadian melting pot, where Indigenous peoples and Old World immigrants cross the boundaries of ethnicity, class, and culture. Like New York's Lower East Side, the North End is also the place that helped to forge Winnipeg's political identity of resistance and revolt. Award-winning filmmaker John Paskievich grew up in Winnipeg's North End, and for the last forty years he has photographed its people and captured its spirit. Paskievich's films, many made for the National Film Board of Canada, follow the lives of different outsiders, from Slovakian Roma to stutterers. The North End Revisited brings together many of the photographs from Paskievich's now-classic book The North End (2007) with eighty additional images to present a deep and poignant picture of a special community. Texts by art critics Stephen Osborne and Alison Gillmor and film scholar George Melnyk explore the different aspects of Paskievich's work and add context from Winnipeg's history and culture."--